‘VACCINE DIPLOMACY’ AND ‘VACCINE NATIONALISM’ IN THE POSTCOVID-9 ERA: AN APPRAISAL FROM THE BANGLADESHI PERSPECTIVE - Datta, Sujit Kumar (SPEKTRUM, 2022)
The impact of global political actors on vaccine diplomacy and vaccine nationalism will be discussed in depth in this research study. First, vaccine pulls in developed countries long before vaccines were discovered and manufactured. Second, vaccine diplomacy and nationalism have emerged as a new tool for safeguarding inter-state relations; it is a weapon for extending imperialism in contemporary international politics. As a result, many governments have competed to announce vaccine gifts or advance supplies to other countries to sway public opinion while failing to meet their needs. For example, the Seram Institute of India failed to produce the promised vaccine due to the severe corona infection and complete failure of the death-oxygen-health system in India. As a result, 1.3 million people out of 3.5 million who received the first dose could receive the second dose. Bangladesh's government has stepped up diplomatic efforts outside India to gather and manufacture vaccines with Russia and China. Furthermore, Bangladesh's government is stepping up diplomatic attempts to obtain vaccines from the USA, Japan, and the UK. Finally, this study will examine how vaccine diplomacy and vaccine nationalism work in Bangladesh regarding vaccine collection. Keywords: Diplomacy, Nationalism, Negotiation, Globalization, Pandemic, Covid-19AbstrakArtikel ini membahas tentang Dampak aktor politik global terhadap diplomasi vaksin dan nasionalisme vaksin. Pertama, penarikan vaksin di negara maju jauh sebelum vaksin ditemukan dan diproduksi. Kedua, diplomasi vaksin dan nasionalisme telah muncul sebagai alat baru untuk menjaga hubungan antar negara; itu adalah senjata untuk memperluas imperialisme dalam politik internasional kontemporer. Akibatnya, banyak pemerintah bersaing untuk mengumumkan hadiah vaksin atau memajukan pasokan ke negara lain untuk mempengaruhi opini publik sementara gagal memenuhi kebutuhan mereka. Misalnya, Institut Seram India gagal memproduksi vaksin yang dijanjikan karena infeksi korona yang parah dan kegagalan total sistem kesehatan oksigen kematian di India. Akibatnya, 1,3 juta orang dari 3,5 juta yang menerima dosis pertama dapat menerima dosis kedua. Pemerintah Bangladesh telah meningkatkan upaya diplomatik di luar India untuk mengumpulkan dan memproduksi vaksin dengan Rusia dan China. Selain itu, pemerintah Bangladesh meningkatkan upaya diplomatik untuk mendapatkan vaksin dari Amerika Serikat, Jepang, dan Inggris. Terakhir, penelitian ini akan mengkaji bagaimana diplomasi vaksin dan nasionalisme vaksin bekerja di Bangladesh terkait pengumpulan vaksin.Kata kunci: Diplomasi, Nasionalisme, Negosiasi, Globalisasi, Pandemi, Covid-19